2014
DOI: 10.2169/internalmedicine.53.1785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Procalcitonin as a Marker of Sepsis: A Potential Predictor of Causative Pathogens

Abstract: Objective Sepsis is one of the leading causes of mortality in critically ill patients, and providing a timely diagnosis and early intervention is necessary for successful treatment. Procalcitonin (PCT) may be a better marker of sepsis than conventional inflammatory markers. The aim of this study was to evaluate the clinical utility of the PCT level as a marker of sepsis. Methods Forty-five patients with sepsis, 24 patients with pneumonia who did not meet the SIRS criteria (PN) and 56 controls were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…[1213] PCT levels have been shown to be able to distinguish Gram-negative bacterial (Gram-negative) sepsis from Gram-positive bacterial (Gram-positive) and fungal sepsis. [10141516] Here, we evaluated the diagnostic accuracy of different inflammatory markers to discriminate sepsis caused by different pathogens within a large patient population.…”
Section: Introductionmentioning
confidence: 99%
“…[1213] PCT levels have been shown to be able to distinguish Gram-negative bacterial (Gram-negative) sepsis from Gram-positive bacterial (Gram-positive) and fungal sepsis. [10141516] Here, we evaluated the diagnostic accuracy of different inflammatory markers to discriminate sepsis caused by different pathogens within a large patient population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although we found a positive correlation between CRP and PCT levels, the fact that both parameters did not differ between the sepses caused by gram+ and gram-bacteria also supports our conclusion. Nakajima et al (27) demonstrated in their study that PCT levels were higher in sepsis patients with gramfactor than the group with gram+ factor. However, because they stated as a limitation of their work that they made this comparison with only 7 gram+ and 6 gram-cases, their results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 92%
“…PCT appears to have higher specificity and sensitivity for predicting bacterial infection than other markers [4,5]. Serum PCT levels differ in patients and are significantly elevated with GN bacteremia [6,7]. CRP, a kind of acute phase reactive protein synthesized by the liver, can regulate inflammatory reaction and defense mechanisms against infectious diseases [8].…”
Section: Introductionmentioning
confidence: 99%